2022
DOI: 10.1101/2022.06.20.22275994
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterising patterns of COVID-19 and long COVID symptoms: Evidence from nine UK longitudinal studies

Abstract: Multiple studies across global populations have established the primary symptoms characterising COVID-19 (Coronavirus Disease 2019) and long COVID. However, as symptoms may also occur in the absence of COVID-19, a lack of appropriate controls has often meant that specificity of symptoms to acute COVID-19 or long COVID, and the extent and length of time for which they are elevated after COVID-19, could not be examined. We analysed individual symptom prevalences and characterised patterns of COVID-19 and long CO… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
(34 reference statements)
6
3
0
Order By: Relevance
“…The duration of PCC was slightly longer in the phenotype with a higher number of symptoms. This in line with the findings of the study by Bowyer et al (2023), where the cluster with a higher burden appeared to be more common in individuals who had a COVID-19 infection more than 12 weeks before the study. There was no difference in the hospital admission rates between the phenotypes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The duration of PCC was slightly longer in the phenotype with a higher number of symptoms. This in line with the findings of the study by Bowyer et al (2023), where the cluster with a higher burden appeared to be more common in individuals who had a COVID-19 infection more than 12 weeks before the study. There was no difference in the hospital admission rates between the phenotypes.…”
Section: Discussionsupporting
confidence: 91%
“…In the phenotype with the highest number of symptoms, HRQoL was the poorest and healthcare use was the highest. This finding is consistent with the results of a study by Bowyer et al (2023) in which data from 9 longitudinal studies were used in a latent class analysis. Based on an extensive set of symptoms, they identified two patterns, one with a low prevalence of symptoms and the other with a higher prevalence of symptoms [27].…”
Section: Discussionsupporting
confidence: 91%
“…The variety of clinical manifestations of Long Covid has led to the suggestion that there may be distinct subtypes of the disease, possibly with differing immunological mechanisms or other aspects of pathophysiology. 23 Our latent class analysis found that a two class model had the best fit with the data, consistent with longitudinal cohort analyses 24 and symptom tracker apps. 8 This is different from the results from Subramanian et al 5 who found that a 3 class model was preferable.…”
Section: Symptoms Following Covid-19 Diagnosissupporting
confidence: 74%
“… 25 Furthermore, in a recent review of nine UK longitudinal studies in adults, totalling over 42,000 participants, the symptoms characteristic of long COVID were similar to the commonest symptoms we describe in CYP, including fatigue, shortness of breath and muscle pain or aches, but also difficulty concentrating and chest tightness. 26 …”
Section: Discussionmentioning
confidence: 99%